Pain indicators in brain-injured critical care adults: An integrative review - Roulin, M.; Ramelet, Anne-Sylvie (2012)
Introduction: Health professionals are confronted with the difficulty of adequately evaluating pain in critically ill, brain-injured patients, as these patients are often unable to self-report. In addition, their confused and stereotyped behaviours may change their responses to pain; the indicators and descriptors generally used to evaluate pain in the critically ill may therefore not be appropriate for brain-injured patients. Aim: The aim of this integrative review was to identify clinically measurable and observable pain indicators and descriptors for brain-injured, critically ill adults. Method: A search of electronic databases (Medline, CINAHL, Embase) combined with cross-referencing was performed. Articles were included if they described pain indicators in critically ill adults and included brain-injured patients in their population. Results: Seven articles met the inclusion criteria. They were critically appraised for their quality and their relevance for the population of brain-injured patients. Behavioural pain indicators such as facial expressions, body movements and muscle tension were found in all of the articles. However, the descriptions of the indicators differ from one article to another. The intensity and nature of behavioural pain responses vary according to the level of consciousness. Changes in physiological parameters have also been reported, but these results are inconclusive. Conclusion: Additional research is needed to identify and better describe pain indicators that are specific to brain-injured patients in the ICU. Studies with large samples, different brain injury diagnoses and various levels of consciousness are warranted.